Kesejahteraan Ayam Petelur di PT Inti Tani Satwa Kabupaten Maros: Welfare of Layer (Case Study: PT. ITS, Maros Regency, South Sulawesi) - Dirga Pranata; Ayu Lestari (Anoa: Journal of Animal Husbandry, 2022)
Animal welfare relates to physical and mental states that conform to the natural behavior of animals and need to be implemented to protect animals. Laying hens are very vulnerable to violating animal welfare principles because of high production targets but demands to minimize costs. The study was conducted in the laying hens of the grower phase of PT. ITS with direct observations, interviews, and discussions. The results were analyzed descriptively according to five principles of animal welfare, namely freedom from pain, injury, and disease, freedom from hunger and thirst, freedom from heat and discomfort, freedom from fear and suffering, and freedom to express normal and natural behavior. The results show that the implementation of animal welfare at PT. ITS has been carried out, but there are also aspects that are not fulfilled, namely the aspect of being free to express normal and natural behavior that has not been fully implemented because the density of the rang or cage makes the animals very crowded so this must be corrected so that the livestock welfare aspects can be met.